Pengaruh Kunjungan Wisatawan Asing dan Investasi Terhadap Penyerapan Tenaga Kerja Serta Pertumbuhan Ekonomi - Damayanti, Ni Luh Emi; Kartika, I Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
Economic growth is an important indicator to look at the success of the economy of a country. The high investment and rapid growth of the tourism sector can trigger high employment and economic growth in an area. The purpose of this study was to determine the effect of foreign tourists and investment to economic growth through employment in the province of Bali. This research was conducted in the province of Bali. Data collected through the documents contained in the BPS Bali. The data used in this research is secondary data is data time series that began in 1995 until 2014. The analysis technique used in this research is the analysis of lane or path analysis. Based on the analysis result that foreign tourist arrivals, and investment positive and significant impact directly on employment. Visits foreign tourists, investment and employment positive and significant impact directly on economic growth, investment and foreign tourists visit also had an indirect effect on economic growth through employment in the province of Bali.
Keywords: Foreign tourist visits; investment; employment; economic growth